Application of Sustainable Intensification (SI) Technologies Among Farmers Interacting With Africa Rising - Michigan State University (International Food Policy Research Institute, 2021)
This dataset was generated from the study conducted to determine whether there is any significant difference in the uptake of sustainable intensification (SI) technologies by farmers because of their interaction with the research team during project implementation. Africa RISING project started interacting with farmers during the 2012/13 cropping season in three agro-ecologies in central Malawi. International Maize and Wheat Improvement Center (CIMMYT) started interacting with farmers who were using conservation agriculture-based SI technologies since the 2007/2008 cropping season in three agro-ecologies in central Malawi. In this study, both CIMMYT and Michigan State University (MSU) led trials were selected. Over time, some new farmers were engaged, creating an opportunity to also study exposure time as a factor to understand the intensity and use of SI technologies. We grouped farmers into two categories to assess the effect of exposure time: (1) farmers who were engaged at the onset of the project (2012/2013), and (2) farmers who were engaged starting 2016/2017 cropping season. Farmers were primarily engaged at different levels. I. Mother trial farmers ? these were farmers who hosted fully replicated trials with a range of technologies, often more than 8 treatments. They were a nucleus group of farmers, who anchored the learning process. They were visited more by researchers and often hosted field days. Farmer interaction with researchers and extension was rated as ?high?. Three mother trials per agroecology were selected for the determination of water-limited yield potential. II. Mother trial farmer experimenter ? these were the same host farmers who were applying SI technologies on their wider farms. Three fields were selected to capture yield data from these. III. Baby farmers: These were a selected group of farmers who were associated with a mother trial. These farmers usually participated in field days and engaged with extension staff. IV. Local controls: These farmers were located in the same village as the mother and baby trial farmers. They did not directly benefit from Africa RISING but were exposed to Africa RISING technologies through field days. They often did not directly relate to the project. At least 3 local controls per mother (3x3 = 9 farmers per agro-ecology) were chosen.